2002
DOI: 10.1002/aoc.301
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis, characterization and polycondensation of metal‐containing diols: crystal structure of [(η5‐C5H5)(CO)2Fe(CH2)3O‐{2,6‐(CH2OH)2‐4‐CH3C6H2}]

Abstract: The synthesis of two new transition‐metal‐containing polyesters is described. The precursors are bifunctional organometallic monomers that were synthesized using 2,6‐bis(hydroxymethyl)‐p‐cresol as the key reagent. This was achieved by simple coupling reactions between the appropriate organometallic alkyl halide and the cresol reagent. Polycondensation reactions were carried out with terephthaloyl chloride using ambient temperature solution techniques. The new low molecular weight oligomeric polyesters were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, A–B type monomers can be designed with organometallic groups capable of MIR acting as (A) and neutral phosphine ligands acting as (B). To explore the possibility of this new polymerization concept, cyclo­penta­dienyl­iron­carbonyl (Fp) chemistry is used for the synthesis of monomers and MCPs. , It is well-known that the reaction of alkyl­di­carbonyl­cyclo­penta­dienyliron (FpR) with nucleophilic ligands, e.g. phosphine (PR 3 ), leads to air stable phosphine coordinated acyl complexes as a result of MIR .…”
mentioning
confidence: 99%
“…For example, A–B type monomers can be designed with organometallic groups capable of MIR acting as (A) and neutral phosphine ligands acting as (B). To explore the possibility of this new polymerization concept, cyclo­penta­dienyl­iron­carbonyl (Fp) chemistry is used for the synthesis of monomers and MCPs. , It is well-known that the reaction of alkyl­di­carbonyl­cyclo­penta­dienyliron (FpR) with nucleophilic ligands, e.g. phosphine (PR 3 ), leads to air stable phosphine coordinated acyl complexes as a result of MIR .…”
mentioning
confidence: 99%
“…[266,267] Bifunctional hydroxyl monomers functionalized with rhenium or iron complexes were reacted with terephthaloyl chloride to produce low-molecular-weight polyesters as shown in Scheme 59. [267] It has been reported that in the presence of UV light, pentacarbonyliron will react with polymers containing silole units in their backbones resulting in the coordination of tricarbonyliron to some of the silole rings. [268] Bunz and coworkers have reported the synthesis of tricarbonylmanganese-coordinated polymers by coupling reactions of substituted cyclopentadienyltricarbonylmanganese complexes.…”
Section: Polymers Containing Metal Carbonyl Complexesmentioning
confidence: 99%
“…A wide range of metal carbonyl compounds containing poly­merizable groups has been synthesized and polymerized using well‐developed polymerization techniques, e.g. free radical polymerization, condensation polymerization and oxidation polymerization . These efforts usually lead to polymers with poor structure characterization, mainly because the metal carbonyl complexes are not stable and not compatible with various polymerization conditions.…”
Section: Introductionmentioning
confidence: 99%